Tingkat Pengetahuan Mahasiswa Pendidikan Profesi Ners tentang Penerapan Dokumentasi Keperawatan Berbasis 3S (SDKI, SIKI, SLKI) - Hasriana; Fitriya Handayani; Rahmatuz Zulfia; Gusni Fitri (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2026)
The application of 3S-based nursing documentation (SDKI, SIKI, SLKI) is a standard of professional nursing practice in Indonesia. Professional Nurse Education students as prospective professional nurses must have adequate knowledge about 3S. To analyze the knowledge level of Professional Nurse Education students on the application of 3S-based nursing documentation. This study used a quantitative descriptive design with a cross-sectional approach. The sample was 33 Professional Nurse Education students selected by total sampling technique. All respondents (100%) had knowledge in the good category with an average score of 16.85 ± 0.44 out of a maximum score of 17. Knowledge per component showed: SDKI 93.5%, SIKI 94.7%, SLKI 95.5%, and documentation application 95.5%. The main initial obstacle in using 3S was difficulty in determining the correct diagnosis (35%), but after learning, 81.8% of students no longer experienced difficulties. Professional Nurse Education students have excellent knowledge about the application of 3S-based nursing documentation. Continuous mentoring is needed to optimize the application of knowledge in clinical settings.